Optimalisasi Kapasitas Stasiun Kerja dengan Metode Theory of Constraints (TOC) di PT. XYZ - Paramitha, Aditya; Aryanny, Enny (BRILIANT: Jurnal Riset dan Konseptual, 2024)
PT. XYZ is a company that produces rims cars. One of the products produced is rims with ABC type. The production process carried out is make to order repetitive. PT. XYZ has a production capacity problem, causing an unfulfilled order. The production floor has a bottleneck work station at work stations 1 and 2. The accumulation occurs because of the standard time difference and the maximum capacity. This study uses the Theory of Constraints (TOC) method to deal with bottlenecked work stations. Calculating the maximum capacity of each work station results in work station s 1 and 2 having less capacity than the other work station. To solve the bottleneck problem at work stations 1 and 2, there are two alternative solutions, overtime and the addition of a work shift. After analyzing the existing problem, to solve bottlenecks at work station s 1 and 2, add the shift of work from 2 shifts to 3 shifts with an overtime of 1 hour per shift.